Strategic Management Of Self-Help Housing Stimulant Assistance (Bsrs) At The Public Works And Spatial Planning Office Of The City Of Sukabumi 2020 - 2022 - Rahayu, Adinda Fauziah; Basori, Yana Fajar FY; Meigawati, Dine (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Self-help Housing Stimulant Assistance or abbreviated as BSRS, is an uninhabitable housing assistance program organized by the Office of Public Works and Spatial Planning throughout Indonesia. The purpose of this study is to find out the Management of the Self-Help Home Stimulant Assistance Strategy (BSRS) at the Public Works and Spatial Planning Office of Sukabumi City 2020-2022. The research began with the discovery of problems, one of which was that the BSRS target had not been able to achieve targets such as the Medium Term Development Plan (RPJMD) and that there were eligible beneficiaries but had not been registered in the Integrated Social Welfare Data (DTKS). The theory used in this research is strategic management theory put forward by L. Wheleen, et al (2015: 48). The method used in this study is qualitative with a descriptive approach, and data collection through observation, interviews and documentation. The results of this study indicate that the method or method used by the Public Works and Spatial Planning (DPUTR) Sukabumi City Office of Public Works and Spatial Planning (DPUTR) has not been optimal, such as socializing the BSRS program that has not been evenly distributed, there are people or prospective beneficiaries who know and do not know the BSRS program. influenced by the information he got, did not have a special procedure regarding the BSRS made by the Sukabumi City DPUTR. But in terms of structure and implementation it has been implemented.